Analysis Of Factors Affecting Healthcare Workers’ Readiness For The Implementation Of Electronic Health Records In The Outpatient Department Of Dr. M. Yunus General Hospital, Bengkulu, In 2025 - Ingga Rahmadani; Fiya Diniarti; Firman Bintara Maju Harianja (Journal Hygeia Public Health, 2026)
The implementation of Electronic Medical Records (EMR) became a national mandate according to Minister of Health Regulation No. 24 of 2022, but the readiness of human resources (HR) is the key to successful implementation. This study aims to analyze the level of readiness of health workers in the Outpatient Department of RSUD dr. M. Yunus Bengkulu in facing the implementation of EMR. The method used in this study is a quantitative method with a Cross-Sectional approach. The research sample consisted of 52 health workers in the Outpatient Department. Data collection was conducted through a structured questionnaire covering variables such as education level, years of service, profession, training history, and facilities and infrastructure. Univariate analysis results showed that out of 52 respondents, most of the respondents, 28 (53.8%), were not ready in terms of the health workers' readiness for EMR implementation. There was no correlation between the level of education and the readiness of health workers in the implementation of Electronic Medical Records (EMR) in the Outpatient Department of RSUD dr. M. Yunus Bengkulu. The education level of healthcare workers in the outpatient department of RSUD dr. M. Yunus Bengkulu is dominated by higher education. There is a relationship between work tenure, profession, training history, and facilities with the readiness of healthcare workers in the Implementation of Electronic Medical Records (EMR) in the Outpatient Department of RSUD dr. M. Yunus Bengkulu in 2025. It is known that the variable of facilities is the dominant variable among the factors of healthcare worker readiness in the implementation of Electronic Medical Records (EMR) in the Outpatient Department of RSUD dr. M. Yunus Bengkulu in 2025. The implementation of Electronic Medical Records (EMR) in the Outpatient Department of RSUD dr. M. Yunus Bengkulu requires improvement of infrastructure, facilities, and structured technical training to optimize the existing healthcare workers.